Cadmium bioaccumulation and detoxification mechanisms in Pomacea insularum: implications for biomonitoring in freshwater ecosystems - Yap, Chee Kong; Al-Mutairi, Khalid Awadh (Frontiers in Environmental Science, 2025)
This study aimed to investigate cadmium (Cd) bioaccumulation and detoxification mechanisms in Pomacea insularum, based on specimens collected from 13 field populations in Peninsular Malaysia and transplantation experiments between polluted and unpolluted sites. Cd concentrations were analyzed in eight tissues, including the cephalic tentacle (CT), pineal sac (PS), digestive tract (DT), and shell, to determine their roles in metal uptake, storage, and excretion. The highest Cd concentration was recorded in the PS (13.5 mg/kg dry weight), while followed by the shells (5.91 mg/kg dry weight), indicating its role as a long-term sequestration site. Notably, the PS showed exceptionally high Cd accumulation, suggesting its potential as a sensitive biomarker for prolonged exposure. The transplantation study revealed that snails relocated from unpolluted to polluted sites accumulated Cd up to 5.22 mg/kg, while those transferred from polluted to unpolluted environments retained Cd between 1.00 and 6.03 mg/kg, indicating slow depuration and tissue-dependent retention. Correlation and regression analyses demonstrated significant interactions among soft tissues, with filtering and digestive organs playing a primary role in detoxification, while calcified structures contributed to long-term Cd sequestration. These findings highlight P. insularum as an effective biomonitor for assessing environmental Cd contamination and bioavailability, providing insights into both short-term exposure and long-term metal storage. Overall, this study reinforces the suitability of P. insularum in biomonitoring programs by demonstrating its ability to accumulate and retain Cd across different human activities. The exceptionally high Cd retention in specific tissues, particularly the PS, highlighting the importance of targeted tissue analysis for pollution assessment. Integrating P. insularum into long-term monitoring strategies can provide valuable data on contamination trends, aiding environmental management and freshwater ecosystem conservation.